Effect of oxygen atmosphere on the morphology of LiTaO3 thin films prepared from polymeric precursor method - Gonzalez, AHM; Simes, A. Z.; Zaghete, M. A.; Varela, José Arana [UNESP] (Amer Ceramic Soc, 2003)
Lithium tantalate (LiTaO3) thin films with (50:50) stoichiometry were prepared using polymeric organic solution. The 5-layered films were deposited on silicon (100) substrates by spin coating method. The coated substrates were thermally treated at 500degreesC for 3 h under several oxygen atmospheres in order to study the influence of oxygen flow on the crystallinity, microstructure, grain size and roughness of the final film. X-ray diffraction results showed that an oxygen flow of 100 cm(3)/min leads to LiTaO3 thin films with higher crystallinity, without preferential orientation. It was observed by scanning electron microscopy (SEM) that the thickness of thin films decreases when the oxygen flow increases. The atomic force microscopy (AFM) studies showed that the grain size and roughness are strongly influenced by oxygen flow.